The role of the Gerontologist in the fight against Ageism - Casanova, Giuliana (2020)
The progressive aging of societies is an unavoidable phenomenon that tends to be accentuated due to the scientific advances and the improvement of living conditions that allow people to live longer. But if the achievements in terms of years of life are, themselves, positive, they are accompanied by a set of prejudices associated with age. Thus, ageism has become a present reality, both in speeches and in practices. Gerontologists, as professionals with theoretical and practical knowledge on aging have an ethical and moral duty to fight ageism. This is intended to be accounted for in this article.